2020
DOI: 10.1111/jfbc.13250
|View full text |Cite
|
Sign up to set email alerts
|

The role of mTOR and oral intervention of combined Zingiber officinaleTerminalia chebula extract in type 2 diabetes rat models

Abstract: The present study examined the potential of Zingiber officinale‐Terminalia chebula extract alone (ZO and TC) and in combination (ZOTC) against type 2 diabetes via downregulation of mechanistic target of rapamycin (mTOR). The 1:4 (ZOTC) ratio showed high cell survival percentage against the rat insulinoma cell line (RIN‐5F) when compared to other possible ratios of ZOTC. Oral administration of ZO alone, TC alone, combined ZOTC (1:4), and the positive control metformin (Met) in fructose‐streptozotocin (STZ) ‐ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, fructose intake upregulates S6 phosphorylation, a marker of the mTORC1 signaling pathway, in muscle and liver tissues [ 147 ]. Another study showed that mTORC1 protein levels were increased in the pancreatic tissue of rats with diabetes induced by fructose-streptozotocin [ 148 ]. A recent report showed that fructose enhanced the production of pro-inflammatory cytokines in response to LPS by increasing mTORC1 activity in monocytes [ 149 ].…”
Section: Activation Of Mtor Signaling In Lung Function and Chronic Hi...mentioning
confidence: 99%
“…Moreover, fructose intake upregulates S6 phosphorylation, a marker of the mTORC1 signaling pathway, in muscle and liver tissues [ 147 ]. Another study showed that mTORC1 protein levels were increased in the pancreatic tissue of rats with diabetes induced by fructose-streptozotocin [ 148 ]. A recent report showed that fructose enhanced the production of pro-inflammatory cytokines in response to LPS by increasing mTORC1 activity in monocytes [ 149 ].…”
Section: Activation Of Mtor Signaling In Lung Function and Chronic Hi...mentioning
confidence: 99%